EFFORTS TO IMPROVE SYLLABLE READING ABILITY THROUGH LETTER CARD MEDIA IN CLASS B, PELANGI KIDS SCHOOL, TANJUNG KERANGT SCHOOL, ACADEMIC YEAR 2022-2023 - Fitri, Rohmawati (USN Kolaka, 2023)
Kindergarten education has a very important role in developing children's personalities and preparing them to enter the next level of education. Reading is a language skill and is an integratedÂ learning consisting of; recognize letters, words, sounds, meanings and get the essence of what is read. Media is considered important, because children need concreteness. Where one of the principles of learning in PAUD is concreteness. Letter cards are a tool that can be used to convey material by looking at pictures, symbols or letter shapes.